Pengaruh Aktivitas Krim Serbuk Biji Bunga Pukul Empat (Mirabilis jalapa L) Terhadap Penyembuhan Luka Sayat Pada Kelinci Jantan (Orygtolagus cuniculus) - Aji, Nurwani Purnama; Lestari, Gina; Sari, Fievi Mayang (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Four o'clock flower plant (Mirabilis jalapa L.) is empirically used in traditional medicine, one of which can help in healing wounds caused by incisions, where this four o'clock flower plant contains flavonoids, alkaloids, saponins and tannins. This study aims to determine whether four o'clock seed powder cream can help in healing cuts.Â This study is an experimental study, where this research looks at the percentage of healing on the incision wound on the back of male rabbits (Oryctolagus cuniculus) for 7 days after treatment, this treatment consists of 5 treatment groups, namely positive control (Betadin), negative control (cream base), and 3 concentrations of four o'clock flower powder cream with a concentration of 5%, 7.5% and 10% with 5 repetitions, the treatment was carried out twice a day in the morning and evening for 7 days.Â The results showed that the treatment that provided the best effectiveness in providing healing to the cut wound was the positive control (Betadine cream) with a percentage of 96.85% followed by the group with a dose variation of four o'clock flower seed powder cream with a dose variation of 10% with a percentage of 92.08% with significant (p<0.005).